The Influence of Probiotics Addition to the Maintenance Media on the Growth and Survival Rate of Seabass (Lates calcarifer) - Wirdha Listiani; Iskandar Putra; Mulyadi Mulyadi (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2024)
This research was conducted from July to September 2021 for 42 days at the Hall of Brackish Water Fish Seed, Kepulauan Meranti Regency, Riau. This study aims to determine the best dose for addition of probiotics to the maintenance media for the growth rate and survival of seabass. This study used completely randomized design (CRD) of one factor consisting of five levels of treatment and three replications. The treatments applied are (P0) control without probiotics (P1) with a dose of 2.5 mL/m3, (P2) with a dose of 5 mL/m3, (P3) with a dose of 10 mL/m3, and (P4) with a dose of 12.5 mL/m3. Research results show that P4 gives the best results of the water quality such as temperature ranges from 27.67-29˚C; water pH ranges from 6.67-7.37; dissolved oxygen (DO) ranges from 4.9-5.53; and ammonia ranges from 0.00138-0.00513. Absolute weight growth of 11.67 g; absolute length growth of 12.33 cm; specific growth rate of 3.78%; survival of 100%; feed efficiency 104.67%; and food conversion ratio (FCR) of 0.95